Prospek Game Edukasi Dalam Pembelajaran Biologi - Hasyri, Yulia Rezki Nanda; Hajar, Ibnu (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to explore the prospects of using educational games in biology learning. The research method employed is descriptive with a quantitative approach. Data were collected using a Guttman scale questionnaire with